The relationship between Chinese language achievement and Chinese cultural knowledge of junior college students - Koh, Hock Kiat. (2009)
This study was designed to find out in the Singapore context, the relationship between Chinese language achievement and Chinese cultural knowledge of junior college students. The term "Chinese cultural knowledge" in this study is taken as consisting of four parts: Literature knowledge, Historical knowledge, Moral knowledge and knowledge of Chinese Festivals and Customs. The sample of the study comprised of 140 students from four junior colleges.